Managing senior management team boundaries and school improvement: an investigation of the school leader role. Issue 1 (2nd January 2017) - Benoliel, Pascale
Abstract : The present study purpose was to investigate the unique role and activities of school principals in managing their senior management team (SMT) boundaries. The study examined how school principals' internal and external activities mediate the relationship of principals' personal factors from the Big Five typology, the team and contextual characteristics of functional heterogeneity and goal interdependence to SMT effectiveness and school outcomes of teachers' absenteeism, school violence and academic emphasis. The results of the structural equation model from a sample of 92 schools indicate that internal activities fully mediate the relationship between principal extraversion and conscientiousness, SMT functional heterogeneity, intra-and inter-team goal interdependence to SMT effectiveness. The external activities were found to fully mediate the relationship between principal extraversion, SMT functional heterogeneity, intra-and inter-team goal interdependence to school outcomes. By concluding that both internal and external activities remain fundamental to overall effectiveness, this study may provide principals with boundary management techniques and practices. The findings may encourage principals to establish priorities and allocate their time, resources and attention effectively both inward and outward the SMT boundary so as to improve SMT and school outcomes.